Evolution of nickel hyperaccumulation in Alyssum L. - Flynn, T; Thomas Flynn (2013)
Phylogenetic studies are providing powerful new insights into the evolution of complex traits. Metal hyperaccumulation is an unusual and complex physiological trait found in about 500 plant species and is associated with an exceptionally high degree of tolerance of metalliferous soils. Alyssum L. (Brassicaceae) is the largest known hyperaccumulator genus, comprising approximately 188 species distributed throughout the Mediterranean region and south-west Asia. Approximately one-quarter of these are largely restricted to areas of serpentine soils and have the ability to accumulate nickel to high concentrations in shoot tissue. This genus provides a good example in which to study the origins of a complex physiological trait, but its phylogeny is currently poorly understood. To produce a well-resolved phylogenetic tree to investigate the number and timing of origins of nickel hyperaccumulation within Alyssum, DNA sequences were generated for four chloroplast regions (matK, rps16–trnK, trnD–T and trnL–F) from 170 of 255 species in the tribe Alysseae. Additional sequencing was carried out for the chloroplast genes ndhF and rbcL and the nuclear gene PHYA. A Bayesian analysis employing a relaxed uncorrelated lognormal molecular clock and multiple fossil-age calibration points was carried out to reconstruct a time-calibrated phylogeny of this tribe using appropriate outgroups. Optimization of the nickel hyperaccumulation trait onto the resulting phylogenetic tree suggests that nickel hyperaccumulation arose twice in the Alysseae in the late Miocene/early Pliocene: 3.3–8.3 Mya in Alyssum and 6.3–8.8 Mya in Bornmuellera. The single origin in Alyssum is strongly associated with a significant acceleration in net species diversification rate, suggesting the ability to hyperaccumulate nickel could have provided a key evolutionary innovation facilitating rapid range expansion and subsequent species diversification. The scattered distribution of nickel hyperaccumulators across small island-like patches of serpentine soil suggests that allopatric speciation may have driven rapid diversification in this clade.